Practical applications of the philosophy of science : thinking about research - Truran, Peter (SpringerBriefs in Philosophy, 2013)
Explores the practical applicability of the philosophy of science to scientific research, but also considers its relevance to practice within the realms of technology,  design, crafts, and even within the world of arts and the humanities.   The attempt to engage working scientists with the issues raised by the philosophy of science may profitably be extended to examine its applicability to any other fields of knowledge that encompass a problem-solving dimension.   Drawing on his experience as a research and development scientist in the biomedical device industry, the author shows how the principles of the philosophy of science illuminate the research process. The book is structured on the concept of the inspirational text; it consists of short chapters, each of which provides an accessible discussion of an aspect of the philosophy of science. Each chapter concludes with a list of practical pointers towards the development of attitudes and skills which will benefit the student researcher.